EMPOWERMENT OF SOCIAL CAPITAL IN SHAPING THE CHARACTER OF ENTREPRENEURSHIP - Umi Fitria (Universitas Muhammadiyah Semarang, 2018)
Unemployment is a complex issue that needs to be studied and immediately looked for solutions. Social capitalempowerment is widely discussed to solve social problems by using entrepreneurial principles to organize,create, and manage an enterprise in order to achieve social goals. Social capital in the form of groups andnetworks, trust and solidarity, collective action and cooperation, information and communication, socialcohesion and inclusion, and empowerment can be utilized in entrepreneurship education and the establishment ofentrepreneurial character, so as to be able to face competition and adapt to environmental changes.Keywords: Social Capital, Entrepreneurial Character.